LIME AND RICE HULL ASH IN SOIL STABILIZATION - Pramono, Agus
Rice hull ash has been recognized as a useful agent for stabilizing heavy clay. It contains silicous material which acts a pozzolan. This thesis describes a laboratory programme designed to study the stabilizing effect, on a clay having a Plasticity Index of 42, of rice hull ash alone and of rice hull ash in combination with lime. The results show that the addition of rice hull ash to the clay has a beneficial effect on unconfined compressive strength. When used in combination with lime, optimum effect for the ranges investigated is obtained when 10 percent by weight of rice hull ash is combined with 5 percent by weight of lime. This results in a material having an unconfined compressive strength equal to that obtained with 8.5 per cent lime alone. Some socio-economic aspects of the use of rice hull ash in soil stabilization are discussed .